2018
DOI: 10.1016/j.jid.2017.08.042
|View full text |Cite|
|
Sign up to set email alerts
|

NF-κB Participates in Mouse Hair Cycle Control and Plays Distinct Roles in the Various Pelage Hair Follicle Types

Abstract: The transcription factor NF-κB controls key features of hair follicle (HF) development, but the role of NF-κB in adult HF cycle regulation remains obscure. Using NF-κB reporter mouse models, strong NF-κB activity was detected in the secondary hair germ of late telogen and early anagen HFs, suggesting a potential role for NF-κB in HF stem/progenitor cell activation during anagen induction. At mid-anagen, NF-κB activity was observed in the inner root sheath and unilaterally clustered in the HF matrix, which indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…FGF5, a member of the FGF family, is the leading candidate for hair length variation, and it is considered a regulator determining the duration of active hair growth (anagen) and the time of hair follicle regression (catagen) [2022]. Recent studies have showed that VEGFR-2 and transcription factor NF-κB are involved in hair cycle regulation and NF-κB is indispensable for hair follicle stem cell activation, maintenance, and/or growth in mice [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…FGF5, a member of the FGF family, is the leading candidate for hair length variation, and it is considered a regulator determining the duration of active hair growth (anagen) and the time of hair follicle regression (catagen) [2022]. Recent studies have showed that VEGFR-2 and transcription factor NF-κB are involved in hair cycle regulation and NF-κB is indispensable for hair follicle stem cell activation, maintenance, and/or growth in mice [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Ocu-miR-205 can promote the transition of Rex rabbit hair follicles from the growing stage to a degenerative quiescent stage by regulating the expression of related genes and proteins in Notch, BMP and other signal pathways,changing the hair density [49]. Krieger et alused mice model to study the regulation of the NF-kb signal pathway in the hair follicle cycle, and found that the NF-kb signal pathway is essential for the growth and activation of hair follicle stem cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, HFs lacking NF-kB activity do not become growth arrested and in fact progress into anagen, albeit in a delayed manner. 106 Thus, Gata6 may have other downstream mechanisms contributing to HG activation and progenitor expansion that remain unknown.…”
Section: Tr An Scrip Ti On Fac Tor S Of Primed Hfsc S In the Hair Gmentioning
confidence: 99%